Identifying the Origin and Proportional Contribution of Nitrate in the Eastern Kabul Aquifer Using Isotopic Indicators and the BSIMM Model - Abdulhalim Zaryab; Hamid Reza Nassery; Farshad Alijani (علوم محیطی)
Introduction: In the past few decades, nitrate contamination in water resources has become a global environmental problem often caused by urban and agricultural activities. In the past two decades, the capital of Afghanistan, Kabul has experienced rapid urbanization. This rapid urbanization has caused groundwater storage depletion and contamination of nitrate in the Kabul Plain. In the Kabul Plain, groundwater is the only source of drinking water for Kabul city residents. This study aims to determine the different sources of nitrate pollution, investigate the nitrogen transformation processes, and estimate the proportional contribution of various sources of nitrate pollution in groundwater of the Eastern Kabul Plain. Material and Methods: Eighteen groundwater samples were collected from the Eastern Kabul Plain aquifer in November 2020. In-situ parameters such as electrical conductivity (EC), pH, dissolved oxygen (DO), and temperature were measured in the sampling sites. The collected samples for analysis of nitrate and nitrate were transported to the Green Tech Laboratory in less than six hours, and the concentrations of mentioned ions were measured on the same day. The collected samples for analysis of major ions were transported to the Regional Water Organization Laboratory of Tehran, Iran. Nitrate samples for isotopic analysis were shipped to the UFZ laboratory in Germany, where isotopic measurements were carried out using the bacterial denitrifier method. The proportional contribution of nitrate sources was determined using the BSIMM model. Results and Discussion: Kabul city does not have a central sewage collection system, and sewage is disposed of mostly through septic and absorption wells. The groundwater nitrate concentration varied from 4 mg/L to 120.4 mg/L with an average value of 21 mg/L. The values ​​of δ15N-NO3̄ varied from 4.8 ‰ to 20.8 ‰ and the values ​​of δ18O-NO3̄ varied from 0.7 ‰ to 18.6 ‰. The composition diagram of δ18O-NO3̄ and δ15N-NO3̄ was employed to determine the main sources of nitrate in the aquifer. Considering that most of the samples are plotted on sewage and manure area, therefore, urban sewage plays a major role in increasing the concentration of nitrate in the groundwater of Eastern Kabul Plain. Since chloride is a conservative ion and is not affected by environmental factors, the diagram of NO3̄/Cl‾ molar ratio versus Cl‾ was used to identify potential sources of nitrate in the Kabul Plain aquifer. The plot indicated that urban sewage is the primary source of nitrate in the aquifer. The high concentration of dissolved oxygen and nitrate in the groundwater samples indicated the dominance of aerobic conditions in the aquifer and the absence of denitrification. Sewage plays a major role in nitrate pollution of groundwater. Therefore, the rapid urbanization and population growth in the Kabul Plain in the past two decades have caused groundwater nitrate pollution. The uncertainty in nitrate sources estimation has been quantitatively assessed using the uncertainty index (UI90). The results of this study display a relatively high uncertainty for the contribution of nitrate sources, particularly sewage and manure (0.49) and soil organic nitrogen (0.44). Conclusion: Sewage and manure, soil organic nitrogen, and chemical fertilizers are potential sources of nitrate in the Kabul Plain. The Bayesian stable isotope mixing model showed that sewage and manure (69.5%) are the main sources of nitrate pollution in the aquifer. The results indicated that nitrification is the main biogeochemical nitrogen transformation process in the Kabul Plain.